Pengembangan Inventori Kecerdasan Emosional Siswa Sekolah Menengah Pertama di Jawa Timur - M Ramli; Nur Hidayah; Lutfi Fauzan (Faculty of Education Universitas Negeri Malang, 2022)
Abstract: The understanding of national intelligence is important for students because in early adolescence, junior high school students are in a state of lability in emotional development. However, circumstances in the field show that many counselors have difficulty in helping students obtain proper information about such emotional intelligence due to the absence of adequate instruments. The purpose of this study is to develop an inventory of emotional intelligence. For this reason, the design is development research. The stages of its development, the preparation of the construct of characteristics to be measured, the preparation of the instrument grid, the preparation of statement items (items), the implementation of expert considerations, the analysis of expert consideration results, field trials, analysis of the results of field trials and revisions, the preparation of norms and guidelines for the use of instruments, and the preparation of reports. The population of this study was junior high school students in East Java Province with the research sample being 389 junior high school students taken using the multistage technique of cluster random sampling area. The study produced a set of emotional intelligence inventories of East Java Junior High School students with adequate validity and reliability as well as practical five-scale norms for counselors to use in uncovering the emotional intelligence of junior high school students in East Java. Based on these results, it is hoped that further research will be carried out with evidence of predictive validity and the development of guidelines for the use of emotional intelligence inventories for East Java Junior High School students. Abstrak: Pemahaman kecerdasan nasional penting bagi siswa karena pada usia remaja awal, siswa SMP berada pada kondisi labil dalam perkembangan emosi. Namun, keadaan dilapangan menunjukkan banyak konselor mengalami kesulitan dalam membantu siswa memperoleh informasi yang tepat tentang kecerdasan emosional tersebut karena tidak adanya instrumen yang memadai. Tujuan penelitian ini adalah mengembangkan inventori kecerdasan emosional. Untuk itu rancangannya adalah penelitian pengembangan. Tahap-tahap pengembangannya, penyusunan konstruk karakteristik yang hendak diukur, penyusunan kisi-kisi instrumen, penyusunan butir pernyataan (item), pelaksanaan pertimbangan pakar, analisis hasil pertimbangan pakar, uji coba lapangan, analisis hasil uji coba lapangan dan revisi, penyusunan norma dan panduan penggunaan instrumen, dan penyusunan laporan. Populasi penelitian ini adalah siswa SMP di Provinsi Jawa Timur dengan sampel penelitian adalah 389 siswa SMP yang diambil dengan teknik multistages area cluster random sampling. Penelitian menghasilkan seperangkat inventori kecerdasan emosional siswa SMP Jawa Timur dengan validitas dan reliabilitas memadai serta norma skala lima yang praktis untuk digunakan konselor dalam mengungkap kecerdasan emosional siswa SMP di Jawa Timur. Berdasarkan hasil tersebut diharapkan dilakukan penelitian lanjutan dengan bukti validitas prediktif dan pengembangan panduan penggunaan inventori kecerdasan emosional siswa SMP Jawa Timur.